Effect of Neodymium Stimulation on the Dielectric, Magnetic and Humidity Sensing Properties of Iron Oxide Nanoparticles - Casagrande-Denardin, J (Elsevier Ltd, 2020)
Neodymium-doped iron oxide (Nd–Fe2O3) nanoparticles (NPs), synthesized via chemical co-precipitation method where particle size is reduced due to the neodymium doping. The addition of neodymium doping, the applied thermal energy of Fe2O3 changes the dielectric constant and loss. At this juncture, the dielectric constant increases due to the elevation of neodymium concentration and thermal energy which eventually reduces the dielectric value. On comparison of dielectric performance, the pristine Fe2O3 endows a high dielectric constant and loss in comparison to Nd–Fe2O3. Neodymium induces the transition from antiferromagnetic to superparamagnetic. The as-fabricated sensors confirm humidity sensing at different ranges. Fascinatingly, the sensitivity of the sensor has increased owing to the increase of neodymium substitution and decrease of particle size while the response time is decreased. The sensors confirm outstanding performance in corrosive environment and their response and sensitivity time values are respectively 5s and 85%. © 2020 Elsevier B.V.